(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The evaluation of the features of the erythrocyte response to the action of ozone in experiments in vitro was carried out. An increase in the effect of this gas on the parameters of oxygen transport in a suspension of erythrocytes was revealed, which is more pronounced with the addition of a donor of gas-transmitter nitrogen monoxide (nitroglycerin) and is not observed with the introduction of hydrogen sulfide.Incubation of erythrocyte suspension with ozone causes the development of oxidative stress, which is manifested by an increase in the concentrations of diene conjugates, malondialdehyde, and a decrease in catalase activity, which indicates an overload of antioxidant defense mechanisms. Nitroglycerin and sodium hydrosulfide do not change the activating effect of ozone on the processes of free radical oxidation, however, they activate the enzymatic link of the antioxidant defense catalase.